Understanding patients’ perceptions of chronic illness care, self-management support needs and their relationship with telehealth preferences: a cross-sectional study in Vietnamese primary care - Wim Peersman; Anselme Derese; Peter Pype; Johan Wens; Quynh Anh Le Ho Thi; Minh Tam Nguyen; Quoc Huy Nguyen Vu; Quang Tuan Duong; Len Len Che Thi; Mong Tuyen Ngo Thi; Chi Le Van (BMJ Open)
Objectives Chronic diseases pose significant challenges to primary care, requiring patient-centred strategies to improve chronic care delivery. As telehealth emerges as a promising tool, this study aims to examine patient experiences with chronic care and their preferences for self-management support (SMS) through telehealth services in primary care settings.Design A multicentre, cross-sectional survey was conducted (June–August 2022) using the Patient Assessment of Chronic Illness Care (PACIC), the Patient Assessment of Self-Management Tasks (PAST) and a telehealth preferences questionnaire. Linear regression assessed the association between PACIC and PAST scores. Multivariate logistic regression identified factors associated with telehealth preferences, with variables selected according to Andersen’s model of healthcare utilisation.Settings Five diverse primary care settings in Central Vietnam, operating under Family Medicine principles.Participants 290 individuals with hypertension and/or diabetes managed at primary care for at least 6 months.Results The average PACIC score was 2.52 (SD 0.7); 25.5% rated their care as high quality (PACIC score ≥3). Among PACIC domains, goal-setting and follow-up/coordination domains received the lowest ratings. Participants perceived lifestyle changes as their priority self-management tasks, followed by medical management, communication with providers and coping with disease consequences. Higher PACIC scores were significantly associated with greater engagement across most PAST domains. Live video conferencing and mobile health were the most preferred formats for SMS. Participants strongly preferred remote patient monitoring for medical management (OR 8.8, 95% CI 2.0 to 38.1). Rural residents were more likely to prefer other telehealth modalities (ORs 3.8–4.6), particularly for coping with disease consequences (OR 4.1, 95% CI 1.8 to 9.4) and lifestyle changes (OR 5.8, 95% CI 1.1 to 28.9). Telehealth preferences were associated with factors across Andersen’s domains, including education (predisposing), resident area and digital access (enabling), and pill count, disease control, and perceived care quality (need-related).Conclusions Most elements of the chronic care model remained unmet. Patients’ care experiences and self-management priorities aligned with their telehealth preferences, underscoring the need for personalised telehealth strategies to enhance SMS in primary care. Given the cross-sectional design and absence of patient and public involvement, further studies should incorporate these stakeholders and confirm associations in more diverse and underserved populations.